2011
DOI: 10.1159/000332442
|View full text |Cite
|
Sign up to set email alerts
|

Sports Injuries among Professional Male Athletes in Kuwait: Prevalence and Associated Factors

Abstract: Objectives: To assess a 12-month period and the lifetime prevalence of sports injuries among male athletes according to type of sport, type of injury and its seriousness, and to examine the association of injuries with sociodemographic, lifestyle and preventive factors. Subjects and Methods: In this cross-sectional study, we approached 475 professional athletes participating in ball sports, aged 15 years and older, from 5 sports clubs in Kuwait. Of them, 452 responded. Four ball games - football (soccer), bask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
2
7
0
1
Order By: Relevance
“…Regarding the type of injuries, this study showed that the most common type of injuries before the quarantine was muscle strain/tears (26.2%), while bruises (28.6%) were the most common type during the quarantine, which were likely due to respondents practicing more light activities and a decrease in extreme forms of activities. A similar study conducted in Brazil had a similar finding in that before quarantine, muscle injuries accounted for 45.4% of injuries, while bruises only accounted for 5.3% [20]. A different study reported that joint injuries (43.6%) comprised the majority of injuries, followed by muscle strains (27.7%), making bruises (26.7%) the third most common form of injury [21].…”
Section: Discussionsupporting
confidence: 51%
“…Regarding the type of injuries, this study showed that the most common type of injuries before the quarantine was muscle strain/tears (26.2%), while bruises (28.6%) were the most common type during the quarantine, which were likely due to respondents practicing more light activities and a decrease in extreme forms of activities. A similar study conducted in Brazil had a similar finding in that before quarantine, muscle injuries accounted for 45.4% of injuries, while bruises only accounted for 5.3% [20]. A different study reported that joint injuries (43.6%) comprised the majority of injuries, followed by muscle strains (27.7%), making bruises (26.7%) the third most common form of injury [21].…”
Section: Discussionsupporting
confidence: 51%
“…Similarly, Shipherd (2010) found that American National Football League players, on average, experience at least one injury a year. In a study of professional male athletes in Kuwait, 74 percent of athletes reported at least one sports injury in the last 12 months, and 90 percent reported having at least one injury in their lifetime (Marwan et al., 2012). In their study, lower limb injuries were the most common site of injury and joint injuries were the most common type.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Voleybol, basketbol ve futbol gibi sıçrama ve ani dönüşlerin olduğu branşlarda kadın sporcuların erkek sporculara göre yaralanma oranları 4-6 kat daha fazladır (1). Voleybolda sporcular genellikle alt ekstremiteye yönelik yaralanmalar yaşamaktadır (2). Dizde ön çapraz bağ (ACL) yaralanmalarının beşte dördü temassız hareketler sonucunda sıçradıktan sonra yere iniş anında gerçekleşmektedir (1).…”
Section: Introductionunclassified